Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/ejic.201190000
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble and Biocompatible Cyclometalated Iridium(III) Complexes: Synthesis, Luminescence and Sensing Application (Eur. J. Inorg. Chem. 2/2011)

Abstract: The cover picture shows the structures of two novel water‐soluble cyclometalated iridium(III) complexes with good water solubility, high quantum efficiency and biocompatibility. Preliminary experiments of cell viability and sensing of lectin show that iridium(III) complexes with appended sugar groups provide advantages of reducing the toxicity and of improving the solubility in water, and open up the possibility of molecular targeting of carbohydrate‐binding domains in cells and tissues. Details are discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…These complexes are highly versatile since neutral [7][8][9][10][11][12], cationic [13][14][15][16][17], anionic [18,19] but also soft salts [20,21], in which both the ion-paired anionic and cationic iridium complexes can participate to light emission, were successfully used as triplet emitters for OLEDs. These complexes also benefit from several appealing features including high quantum yield of luminescence [22,23], phosphorescence at room temperature [24] and relatively short excited state lifetimes so that key adverse factors such as triplet-triplet annihilation and back energy transfer from the guest to the host are strongly limited [25][26][27][28]. Emission color can also be easily tune by mean of the ligands introduced in the coordination sphere of the metal cation, enabling the emission to range from blue to red [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 97%
“…These complexes are highly versatile since neutral [7][8][9][10][11][12], cationic [13][14][15][16][17], anionic [18,19] but also soft salts [20,21], in which both the ion-paired anionic and cationic iridium complexes can participate to light emission, were successfully used as triplet emitters for OLEDs. These complexes also benefit from several appealing features including high quantum yield of luminescence [22,23], phosphorescence at room temperature [24] and relatively short excited state lifetimes so that key adverse factors such as triplet-triplet annihilation and back energy transfer from the guest to the host are strongly limited [25][26][27][28]. Emission color can also be easily tune by mean of the ligands introduced in the coordination sphere of the metal cation, enabling the emission to range from blue to red [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 97%
“…To enhance the water solubility, ECL intensity, and/or binding specicity of Ru(II) and Ir(III) complex electrochemiluminophores, researchers have incorporated 4,7-diphenyl-1,10-phenanthroline-disulfonate ligands 17,18 or synthesised new ligands with polar functional groups such as methanesulfonate, tetraethylene-glycol and saccharides. 3,19,20 Comparisons with [Ru(bpy) 3 ] 2+ in the 'ProCell' buffer solution (containing TPrA coreactant and a surfactant) used in commercial ECL immunoassay system, however, have revealed that only a few outperform the conventional luminophore. 18,20,21 One of the most promising candidates, an Ir(III) complex containing two sulfonate-bearing phenylphenanthridine derivatives and a phenylisoquinolinebased ligand for bioconjugation, exhibits 3-4 fold greater ECL intensity than the Ru(II) complex.…”
Section: Introductionmentioning
confidence: 99%
“… Various Ir III complexes previously examined for photoluminescence, chemiluminescence, and/or ECL detection: I : (2,2′‐bipyridine‐κ N 1 ,κ N 1′ )bis[2‐(2‐pyridinyl‐κ N )phenyl‐κ C ]iridium(1+);3b II a , R=H: {[3,3′‐(1,10‐phenanthroline‐4,7‐diyl‐κ N 1,κ N 10)bis(benzenesulfonato)](2−)}bis[2‐(2‐pyridinyl‐κ N )phenyl‐κ C ]iridate(1−);3b, 4c, 6 II b , R=F: bis[3,5‐difluoro‐2‐(2‐pyridinyl‐κ N )phenyl‐κ C ]{[(1,10‐phenanthroline‐4,7‐diyl‐κ N 1 ,κ N 10 )bis(benzenesulfonato)](2−)}iridate(1−);4c, 7 III : {[(2,2′‐bipyridine)‐4,4′‐diyl‐κ N 1 ,κ N 1′ ]bis(methylene)bis(1‐thio‐β‐ D ‐glucopyranoside)}bis[2‐(2‐pyridinyl‐κ N )phenyl‐κ C ]iridium(1+);5b IV : [2‐(1‐methyl‐1 H ‐1,2,3‐triazol‐4‐yl‐κ N 3 )pyridine‐κ N ]bis[2‐(2‐pyridinyl‐κ N )phenyl‐κ C ]iridium(1+);8 V : bis[3,5‐difluoro‐2‐(2‐pyridinyl‐κ N )phenyl‐κ C ]{2‐[1‐(phenylmethyl)‐1 H ‐1,2,3‐triazol‐4‐yl‐κ N 3 ]pyridine‐κ N }iridium(1+),2i, 9 VI : bis[3,5‐difluoro‐2‐(2‐pyridinyl‐κ N )phenyl‐κ C ]{2‐[1‐(phenyl‐4‐sulfonate)‐1 H ‐1,2,3‐triazol‐4‐yl‐κ N 3 ]pyridine‐κ N }iridium 6…”
Section: Introductionmentioning
confidence: 99%